Antitumour activity of resveratrol on human melanoma cells: A possible mechanism related to its interaction with malignant cell telomerase - Platella, Chiara; Guida, Serena; Bonmassar, Laura; Aquino, Angelo; Bonmassar, Enzo; Ravagnan, Giampiero; Montesarchio, Daniela; Roviello, Giovanni N.; Musumeci, Domenica; Fuggetta, Maria Pia (Biochimica et biophysica acta. General subjects, 2017)
trans-Resveratrol (tRES) is a polyphenolic stilbene found in plant products which has attracted great attention because of its antioxidant, anti-inflammatory and anticancer properties. The possible correlation between tRES-induced suppression of melanoma cell growth and its influence on telomerase expression has been investigated by biological assays. Moreover, in order to gain new knowledge about possible mechanisms of action of tRES as antineoplastic agent, its interaction with biologically relevant secondary structure-forming DNA sequences, its aggregation properties and copper-binding activity have been studied by CD, UV and fluorescence spectroscopies. Biological assays have confirmed that growth inhibitory properties of tRES well correlate with the reduction of telomerase activity and hTERT gene transcript levels in human melanoma cells. Biophysical studies in solution have proved that tRES binds all the studied DNA model systems with low affinity, however showing high ability to discriminate G-quadruplex vs. duplex DNA. In addition, tRES has shown no propensity to form aggregates in the explored concentration range and has been found able to bind Cu2+ ions with a 2:1 stoichiometry. From these biological and biophysical analyses it has emerged that tRES produces cytotoxic effects on human melanoma cells and, at a molecular level, is able to bind Cu2+ and cancer-involved G-quadruplexes, suggesting that multiple mechanisms of action could be involved in its antineoplastic activity. Expanding the knowledge on the putative mechanisms of action of tRES as antitumour agent can help to develop novel, effective tRES-based anticancer drugs. [Display omitted] •tRES produces growth inhibitory effects in human melanoma cells dose-dependently.•tRES inhibits telomerase activity and influences the expression of hTERT gene.•Biophysical studies on the interaction of tRES with different DNA model systems.•High ability of tRES to discriminate G-quadruplex vs. duplex DNA.•tRES is able to bind Cu2+, a biologically relevant metal ion.